Spiroplasma culicicola sp. nov. from the Salt Marsh Mosquito Aedes sollicitans† - Hung, Shirley H. Y.; Chen, T. A.; Whitcomb, R. F.; Tully, J. G.; Chen, Y. X. (International Journal of Systematic and Evolutionary Microbiology, 1987)
Spiroplasma strain AES-1, which was isolated from the salt marsh mosquito Aedes sollicitans, is the monotypic representative of group X. This strain differed in serological reactivity, growth pattern, and morphology from previously described spiroplasmas. Most cells of strain AES-1 were nonhelical; helical cells were about 1 to 2 μm long and rarely had more than one or two turns. Optimal growth occurred at 31°C; no growth was observed at 37°C. Cholesterol and amino acids were required for growth. Strain AES-1 utilized glucose, fructose, mannose, mannitol, and trehalose in the chemically defined CC-494 medium, failed to hydrolyze arginine and urea but reduced tellurite either aerobically or anaerobically, and was susceptible to digitonin. Polyacrylamide gel electrophoretic patterns of the cell proteins of strain AES-1 were distinctive and were characterized by a major low-molecular-weight protein band. The guanine-plus-cytosine content was 26.6 mol% as determined by thermal denaturation. Serological studies, using growth inhibition, deformation, and metabolism inhibition tests, showed that strain AES-1 was distinct from all recognized spiroplasma groups and subgroups, including the six named Spiroplasma species; avidin-biotin-peroxidase enzyme-linked immunosorbent assays showed that strain AES-1 was unrelated to S. citri, S. melliferum, S. kunkelii, S. floricola, and S. apis. Strain AES-1 is the first to be characterized biochemically in a chemically defined medium. We propose that strain AES-1 (ATCC 35112) be designated as the monotypic representative of a new species, Spiroplasma culicicola sp. nov.